MOTIVASI PEKERJA TERHADAP PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PROYEK GEDUNG APARTEMEN THE UMALAS SIGNATURE - IDA BAGUS GEDE INDRAMANIK; JUNIADA PAGEHGIRI; WAGE SUARTA (Universitas Mahasaraswati K. Mataram, 2023)
BPJS Employment data revealed that work accidents reached 153,044 cases throughout 2020. Based on the location of the incident, in the work environment work accidents occur as many as 68.5 percent of cases. The provision and use of personal protective equipment is an effort to improve occupational safety and health. Work experience and selection behavior of PPE types affect adherence to PPE use. From the results of an initial survey conducted on August 19, 2022 using the interview method with contractor staff at The Umalas Signature Project in charge of K3, during the project which has been approximately 5 months, no training on K3 has been held for workers even though work accidents are dominant because construction workers are careless and undisciplined in the use of personal protective equipment. There are three factors that can affect the use of personal protective equipment from workers, namely psychological factors, individual factors, and organizational factors. Data was collected by questionnaire and interviews with 39 respondents, then the data was analyzed using quantitative descriptive data analysis methods and scoring analysis. Data analysis was conducted to determine the most dominant factors influencing worker motivation in using personal protective equipment (PPE) and to measure what is the level of motivation of workers in using personal protective equipment (PPE) based on individual, psychological, and organizational factors. The results of this study are the most dominant factors influencing worker motivation in using personal protective equipment (PPE) are organizational factors in the FO 3 statement item with a percentage value of 95% and an average score of 4.5 (very strong). Then based on multiple linear regression analysis tests, Individual Factors showed an influence value of 44.4%. Psychological factors show an influence value of 41.4%. Organizational factors showed an influence value of 67.1%.